The Role of Hepatic Expression of STAT1, SOCS3 and PIAS1 in the Response of Chronic Hepatitis C Patients to Therapy - Sherif El-Saadany; Dina H Ziada; Hanan El Bassat; Wael Farrag; Hesham El-Serogy; Manal Eid; Manal Abdallah; Medhat Ghazy; Hoda A Salem (Canadian Journal of Gastroenterology)
BACKGROUND: The underlying mechanisms of hepatitis C virus (HCV) resistance to treatment are unknown. Signal transducers and activators of transcription (STAT) proteins play a critical role in antiviral defense.